YAP and TAZ Regulate Cc2d1b and Purβ in Schwann Cells - Belin, Sophie; Herron, Jacob; VerPlank, Jordan J. S.; Park, Yungki; Feltri, Laura M.; Poitelon, Yannick (Frontiers in Molecular Neuroscience, 2019)
Schwann cells are exquisitely sensitive to the elasticity of their environment and their differentiation and capacity to myelinate depend on the transduction of mechanical stimuli by YAP and TAZ. YAP/TAZ, in concert with other transcription factors, regulate several pathways including lipid and sterol biosynthesis as well as extracellular matrix receptor expression such as integrins and G-proteins. Yet, the characterization of the signaling downstream YAP/TAZ in Schwann cells is incomplete. Myelin sheath production by Schwann cell coincides with rapid up-regulation of numerous transcription factors. Here we show that ablation of YAP/TAZ alters the expression of transcription regulators known to regulate Schwann cell myelin gene transcription and differentiation. Furthermore, we link YAP/TAZ to two DNA binding proteins, Cc2d1b and Purβ, which have no described roles in myelinating glial cells. We demonstrate that silencing of either Cc2d1b or Purβ limits the formation of myelin segments. These data provide a deeper insight into the myelin gene transcriptional network and the role of YAP/TAZ in myelinating glial cells.